Developing a Digital Module for Integrating Islamic and Muhammadiyah Values with Pancasila in Vocational Education: A Sadiman Method Approach - Pratama Benny Herlandy; Neng Sholihat; Pahmi; Nuur Wachid Abdul Majid; Mohamed Nor Azhari Azman; Abdullah Nasih Ulwan (Universitas Muhammadiyah Surakarta, 2024)
This research aims to produce a module that is relevant to the character of Muhammadiyah Vocational School, namely integrating Islamic and Muhammadiyah values with the Pancasila student profile. This research was a type of development research by applying the Sadiman Development Method. Analysis of the result quality of the developed module was carried out using a validation test from the material aspect and media aspect as well as a trial by respondents to the developed module. The evaluation was conducted by media professionals using a 20-item questionnaire, yielded an average score of 84, indicating a high level of appropriateness. Similarly, material experts assessed the validators using a 30-item questionnaire and found the performance to be highly appropriate, resulting in a score of 89. Based on these findings, it can be stated that the developed digital module has relevant validity values and is suitable to be used in vocational learning which can be integrated with Islamic and Muhammadiyah values. The use of this module has an impact on cultivating Islamic character and Pancasila students for Muhammadiyah Vocational School students. This distinctive character is a provision for alumni to be able to compete in the work world in today's digital era.